2014
DOI: 10.1177/070674371405900503
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Reform at a Systems Level: Widening the Lens on Recovery-Oriented Care

Abstract: This paper is an initial attempt to collate the literature on psychiatric inpatient recoverybased care and, more broadly, to situate the inpatient care sector within a mental health reform dialogue that, to date, has focused almost exclusively on outpatient and community practices. We make the argument that until an evidence base is developed for recoveryoriented practices on hospital wards, the effort to advance recovery-oriented systems will stagnate. Our scoping review was conducted in line with the 2009 Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 69 publications
1
79
0
Order By: Relevance
“…Seven of the nine participants in the smallest activity space size category (<5 km) have lives in these spaces that converge with traditional understandings of community: a physical presence in a geographic area that includes social contact with others and engagement with meaningful places. These participants were strongly connected to cultural or religious communities or social service organizations, which were located in close proximity to their home addresses (ID 15,8,4,2,16,27,28). For these participants, small activity spaces reflected social ties within a local geographic area, consistent with results from previous studies where people with smaller activity spaces were shown to experience a stronger sense of community.…”
Section: Patterns In Activity Spaces: Understanding Presence In the Csupporting
confidence: 82%
See 3 more Smart Citations
“…Seven of the nine participants in the smallest activity space size category (<5 km) have lives in these spaces that converge with traditional understandings of community: a physical presence in a geographic area that includes social contact with others and engagement with meaningful places. These participants were strongly connected to cultural or religious communities or social service organizations, which were located in close proximity to their home addresses (ID 15,8,4,2,16,27,28). For these participants, small activity spaces reflected social ties within a local geographic area, consistent with results from previous studies where people with smaller activity spaces were shown to experience a stronger sense of community.…”
Section: Patterns In Activity Spaces: Understanding Presence In the Csupporting
confidence: 82%
“…The role of discrimination was prominent in shaping this aspect of community participation, resonating with the intense stigmatization of psychoses. 27 Herein lies one of the central dilemmas in the field -whether service environments should cultivate a community ethos (as in early sanitarium models) or strictly emphasize out-of-hospital community participation. Indeed, enhancing community participation is clearly complex, as evidenced by the unclear benefits of public awareness campaigns designed to reduce discrimination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One paper is about physicians being trained to psychiatric/psychosocial rehabilitation (PSR) principles [38]. Several are about improving already established practices for inpatients [39,40], for instance through the implementation of advance directives [41], and at a system's level [42].…”
Section: Resultsmentioning
confidence: 99%